Beyond Self-Report: Performance Measures of Emotional Competencies Predict Symptoms of Depression and Anxiety, Physical Symptoms, Self-Rated Health, and Immunoregulatory Molecules. Issue 6 (20th June 2016) - Tuck, Natalie L.; Grant, Rosemary C. I.; Jackson, Amy; Brooks, Anna E. S.; Consedine, Nathan S.
Abstract: Background: Most work testing links between emotional competencies and health has focused on self-reported and/or trait assessments. However, more objective assessments of skills and knowledge may also predict health relevant outcomes. Purpose: The current study investigated whether performance-based tests of emotional knowledge and expressive skill predicted symptoms of depression and anxiety, self-reported physical symptoms, perceived health, and a range of immunoregulatory molecules. Methods: Eighty females aged 18–35 completed self-report assessments before attending a testing session in which they provided blood samples and completed performance-based assessments of expressive skill and emotional knowledge. Results: Greater expressive skill predicted better self-reported outcomes, but links to immunoregulatory molecules were mixed. Expressive skill for contempt and anger predicted higher, whereas skill for happiness predicted lower, concentrations of immunoregulatory molecules. Conclusions: These data highlight the need to extend research beyond self-reported emotional competencies and suggest that performance-based skill and knowledge metrics may be associated with health relevant outcomes.